The Effect of Swirl Vanes Blade’s Angle towards the Visualization and Temperature Distribution of Co-flow Diffusion Flame - RD Issafira; W Wijayanti; AR Ramadhani; A Tambunan; AN Rahmatullah (Nusantara Science and Technology Proceedings, 2022)
The awakens of the recirculation zone is favorable in the combustion process to enhance the mixing between fuel and oxidizer, since this zone has a turbulence flow. One of the popular ways to create turbulence is by adding a flame obstacle on the co-flow diffusion burner. The flame perturbation used in this study is swirl vanes with different angle variations, which will be installed on the air entrained. The visualizations and temperature distributions of diffusion flame under different swirl blade angle was observed. The variations of 10o , 20o, and 30o swirl blade tilt were applied. The fuel used in this study is methane (CH4) gas. The fuel velocity (uf) varied in this study between 1.3 to 15.9 m/s, whereas the air velocity (ua) was kept constant at 0.9 m/s anf 1.4 m/s. These parameters were applied for each swirl vane’s angle configuration. The results showed that the increment of uf at fixed ua increase the flame height until a certain point, then decreases until the flame blows out. Moreover, the flame color also change from orange to blue with the increment of uf , since the mixture become rich. Furthermore, the larger swirl vanes blade’s angle brings the flame height shorter under all uf variations, due to the appearance of turbulence flow. The temperature distribution of greater angle tilt showed a more homogenous distribution across the flame area and showed higher temperature. This is happened due to the higher mixture reaction between the fuel and air.